Utilization of waste Cappadocia earth as a natural pozzolan in alkali activation: A parametric study - Ozata, Serife; Akturk, Busra; Yuzer, Nabi (ELSEVIER SCI LTD, 2022)
This study presents the investigation of the possible use of rock-cut carving waste earth in Cappadocia as a precursor in alkali activation. The Cappadocia waste earth was activated by sodium hydroxide (NH) and sodium silicate (WG). In addition, slaked lime (CH) was substituted as a calcium resource. The compressive strength development was determined and the reaction mechanisms were investigated through X-ray diffraction and Fourier transform infrared spectroscopy. It was found that different strength levels can be obtained, depending on the activator type and CH-substitution ratio. While WG-activated mixes presented higher early age values, NH-activated mixes presented higher values at further ages, i.e., ~17 MPa at 28 days. The CH substitution enhanced the compressive strength for both early and further ages, attributing to the available Ca2+ ions resulting in the formation of C-A-S-H gel. The XRD results showed that silicates group minerals prominent in control mixes, while C-A-S-H-like gel was the primary phase in CH-substituted mixes. N-A-S-H and other hydrated compounds were found in all mixes, responsible for strength increment. Moreover, secondary electron microscope images revealed a denser structure in WG-activated mixes. Results of energy dispersive spectroscopy and X-ray diffractions corroborated hydration products and alkali activation. The obtained results of this study depict that alkali-activated Cappadocia earth can be a feasible and alternative sustainable binder to be used as a structural material.
Keywords: Natural pozzolan; Alkali-activated materials; Geopolymers; Cappadocia; Compressive strength; Microstructure; INORGANIC POLYMERS GEOPOLYMERS; VOLCANIC ASH; ENGINEERING PROPERTIES; STRUCTURAL CHARACTERISTICS; PORTLAND-CEMENT; SILICA MODULUS; BINDER; METAKAOLIN; Construction & Building Technology; Engineering; Materials Science